Long Circulation of PEG-TRAIL Improves Anti-Hepatic Fibrosis Effect of TRAIL Via Targeting Activated Hepatic Stellate Cells - Lu, Bingyun; Peng, Lijun; Luo, Shenggen; Zhou, Jing’e; Xu, Nan; Dong, Chunxiu; Yan, Zhiqiang; Li, Huiyi; Li, Qinghua (Frontiers in Materials, 2021)
Background: The short half-life of TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) greatly limits its clinical application. This study was aimed to improve its potency on liver fibrosis through PEG (polyethylene glycol) modification prolonging the half-life of TRAIL. Methods: PEG, TRAIL, and the chemically synthesized complex PEG-TRAIL were used to treat 3T3 and LX-2 cells and liver fibrotic mice. In vitro, cell viability, apoptosis, and fibrosis were investigated using CCK-8 (cell counting kit-8) assay, flow cytometry, and western blotting, respectively. In vivo, Sirius red staining, immunohistochemistry, and α-SMA (α-smooth muscle actin)/TUNEL (terminal deoxynucleotidyl transferase dUTP [2'-deoxyuridine 5'-triphosphate] nick end labeling) double-labeling immunofluorescence (IF) were performed after various treatments for liver fibrotic mice. The fibrotic liver was subjected to DR4 (death receptor 4)/TRAIL double-labeling IF to assess the retention of TRAIL enhanced by PEGylation. Results: We found that, the cells treated with PEG-TRAIL showed lower cell viability, higher apoptosis level, and stronger anti-fibrotic effect compared with PEG or TRAIL treatment. In vivo, PEGylated TRAIL exhibited a longer circulation than TRAIL did. Compared with TRAIL treatment, PEG-TRAIL caused a significant reduction of α-SMA and a markedly increase of apoptotic aHSCs. PEGylation is more likely to prolong the retention of TRAIL in circulation and enhance the possibility to target at aHSCs and DR4-positive (DR4+) cells in liver. Conclusion: PEG-TRAIL presents better anti-fibrotic and pro-apoptotic effects, for which, the prolonged circulation half-life in vivo may account. The PEG-TRAIL may serve as a new clinical therapeutic for liver fibrosis in the future.